Parasitic leiomyoma: A rare case report - Mrityunjay Metgud; Kanchibhotla Meghana; Kumar Vinchurkar; Shrishail Metgud; Kamal Patil; Mahadevi Savanur; Vinutha Hanji; Adarsh Sanikop (Journal of Krishna Institute of Medical Sciences University, 2023)
Uterine leiomyomas or fibroids are the most common benign tumors of the female genital tract in the reproductive age group. Parasitic fibroids or wandering fibroids are rare variants of uterine fibroids which present outside the uterus. They are known for their rarity and atypical clinical presentation which can often impose a diagnostic dilemma. Due to increase in the use of minimally invasive surgeries, the incidence of parasitic leiomyoma is rising. We report a case of large parasitic broad ligament fibroid in a 33-year-old lady post hysterectomy. The lady presented with a mass per abdomen, and the firm mass extended deep into the pelvis. Exploratory laparotomy revealed a vascular mass of approximately 2.8 kg and confirmed by histopathological examination as leiomyoma. Post-operatively she was conservatively managed and discharged with a good outcome.